The Normal Force Characteristic of a Novel Magnetorheological Elastomer Based on Butadiene Rubber Matrix Compounded with the Self-Fabricated Silly Putty. (14th December 2021) - Guo, Fei; Du, Chengbin; Yu, Guojun
Abstract : In this paper, a novel magnetorheological elastomer (MRE) was prepared by dispersing carbonyl iron particles (CIPs) into a composite matrix compounded by butadiene rubber (BR) and self-fabricated Silly Putty. The rate-sensitive and magneto-induced characteristics of normal force were experimental investigated to discuss the working mechanism. The results demonstrated that the normal force increased with the compression rate and the mass fraction of boron-silicon copolymer added to the composite matrix due to the formation of the more and more B-O cross bonds which could be blocked in the C-C cross-linked network of BR. Meanwhile, the magneto-induced normal force was positively correlated with the applied magnetic field strength and the compression strain due to the decreased gap between the centers of soft magnetic particles and the increased particle intensity of magnetization. Moreover, the magneto-induced normal force continued to enhance with the increase of compression strain because the CIP chains fixed in the C-C cross-linked network could bend to a radian and CIP chains in B-O cross-linked network could rupture to form more stable and intensive short-chain structures. Besides, a simplified model was deduced to characterize the mechanism of the generation of the magneto-induced normal force. Furthermore, the normal force varied stably with the oscillatory shear strain (less than 9%) at different magnetic induction intensities and suddenly reduced when the applied oscillatory shear strain was more than 9%.